2020
DOI: 10.3991/ijoe.v16i15.17115
|View full text |Cite
|
Sign up to set email alerts
|

Lung Segmentation Using Proposed Deep Learning Architecture

Abstract: <div id="titleAndAbstract"><table class="data" width="100%"><tbody><tr valign="top"><td class="value">The Prediction and detection disease in human lungs are a very critical operation. It depends on an efficient view of the CT images to the doctors. It depends on an efficient view of the CT images to the doctors. The clear view of the images to clearly identify the disease depends on the segmentation that may save people lives. Therefore, an accurate lung segmentation system from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Saif et al (2020) used VGG16 as CNN model to diagnose 1500 of lung cancer images, the result achieve 98.55% of accuracy. Ayad et al (2020) proposed a CT-based lung segmentation method that used the weighted Softmax function. Using the LIDC-IDRI CT lung images database, the system obtained a maximum segmentation accuracy of 98.90%.…”
Section: Introductionmentioning
confidence: 99%
“…Saif et al (2020) used VGG16 as CNN model to diagnose 1500 of lung cancer images, the result achieve 98.55% of accuracy. Ayad et al (2020) proposed a CT-based lung segmentation method that used the weighted Softmax function. Using the LIDC-IDRI CT lung images database, the system obtained a maximum segmentation accuracy of 98.90%.…”
Section: Introductionmentioning
confidence: 99%
“…A few unique sorts of layers are frequently utilized in CNNs [20,21], such as loss, convolutional, ReLu (Rectified Linear Units), pooling, and fully connected layer [22]. Deep neural network used in many fields such as the study [23][24][25][26][27][28].…”
Section: Figure 3 Overview Of a Convolution Neural Network [16]mentioning
confidence: 99%
“…Medical imaging analysis plays a critical role in diagnosing disease such as diabetic retinopathy [19], skin cancer [20] and lung disease [21]. In literature, several studies have been reported for automatic segmentation of myocardial scar and edema.…”
Section: Related Workmentioning
confidence: 99%